ANALISIS TINGKAT KERENTANAN BENCANA TSUNAMI STUDI KASUS KABUPATEN PADANG PARIAMAN - melki melki agestira; Iswandi Umar (JURNAL BUANA, 2022)
This study aims to (1) determine the level of tsunami hazard in Kabupaten Padang Pariaman, (2) determine the level of vulnerability to the Tsunami disaster in Kabupaten Padang Pariaman. The method used is an overlay method with weighted parameters of vulnerability and vulnerability. The results of this research are: (1) The area prone to tsunami disasters in Padangpariaman Regency is an area along the coast of the Indian Ocean. This area is part of Batang Gasan, Sungailimau, Limo Koto Kampung Dalam, Ulakan Tapakis, and Batanganai Districts. This is due to its location on the coast with a sloping topography. Of these areas, Ulakan Tapakis District is the most vulnerable. (2) The area with a high level of vulnerability is Ulakan Tapakis District. This is because most of the area is prone to tsunamis. Coupled with a population that is more dense than the surrounding area. The Batang Gasan, Sungailimau and Batanganai areas are in the medium category. Meanwhile, Limo Koto Kampung Dalam sub-district is included in the low vulnerability class.